European impact on Egyptian industrialization during the rule of Muhammad Ali Pasha (1805-1848) - Samir Ahmeti; Gazmend S. Rizaj (The Journal of European Economic History (JEEH), 2024)
The founding of modern Egypt by Muhammad Ali Pasha required an appropriately modern economy, with industry following the model of more advanced European states. The Pasha of Egypt in- volved himself personally in every phase of the organization of Egyptian industry, garnering the experiences of Western countries - particularly France, Italy, and Britain. It constitutes a rare case of a leader with very little education himself who was yet so interested in the all-encompassing reform of his country. This reform would enable the maintenance of absolute authority and the liberation of Egypt from the Ottoman administration. The Pasha of Egypt himself prompted the sending of hundreds of Egyptian students to professional schools and major universities in Europe in the interests of modern state administration, modern education, a modern Egyptian army, and the country's industrialization. The Pasha was confronted with many difficulties on this course, especially the lack of a cadre adequate for the organization and management of Egyptian industry, and he did not hesitate to engage experts and specialists from European countries - among whom the Italian community, in particular, distinguished themselves, having the most significant impact on the Egyptian economy. Egypt's rapid transformation from traditional artisanal manufacturing to industrialized capitalist production was an enormous challenge. Establishing numerous manufacturing workshops, heavy industry, infrastructure projects, and the development of agriculture and cotton and textile industries brought sub- stantial cultural and socio-economic change. Through Western and Eastern sources and historiography, we aimed to gain insights into the successes and failures of Muhammad Ali Pasha's government during the colossal process of reforming and industrializing Egypt.
Keywords: 330; Industrialization; International Relations; Egypt; Europe; Industrialisierung; Internationale Beziehungen; Ägypten; Europa